The Effectiveness of Translation, Image-based and Video-based Methodologies for Receptive and Productive Vocabulary Acquisition - Bueno Alastuey, Mª Camino; Navarro García, David (Huarte de San Juan. Filología y Didáctica de la Lengua, 2020)
The aim of this study is to analyse and compare three different methodologies (glossed L1 translation, image-based and video-based) for vocabulary learning taking into account the two kinds of vocabulary knowledge: receptive/passive and productive/active. The participants were 52 high school students aged 12 to 15, who were exposed to all the methodologies. The instruments employed for this research were a pre-test to check previous knowledge, three post-tests, one for each methodology, which were administered immediately after the treat-ment and a week later, and a questionnaire. The results indicate that the image-based method-ology seems to be the most effective in terms of immediate and delayed recall, while all three methodologies are equally effective for receptive vocabulary knowledge, and translation and the image-based methodology slightly better for pro-ductive. Even with similar quantitative results, students expressed a greater preference for the image-based methodology.